Amyloid angiopathy in idiopathic Parkinson’s disease. Immunohistochemical and ultrastructural study - Bertrand, Ewa; Lewandowska, Eliza; Stępień, Tomasz; Szpak, Grażyna M.; Pasennik, Elżbieta; Modzelewska, Joanna (Folia Neuropathologica, 2008)
The prevalence of cerebral amyloid angiopathy (CAA) and its association with intellectual decline in idiopathic Parkinson’s disease (iPD) remain unclear. To identify the role of CAA in iPD dementia the prevalence and severity of CAA were investigated, with particular respect to changes in vessel wall structure. Twenty-eight autopsy Parkinsonian brains and fourteen age-matched controls, post-mortem revised histopathologically for the presence of α-synuclein and Alzheimer’s disease (AD)-type pathology, using standardized clinico-neuropathological criteria, underwent further investigation. Histological, immunohistochemical staining methods with antibodies to amyloid β-peptide, α-actin, collagen III, collagen IV and CD34 as well as ultrastructural methods were used. The findings showed that the prevalence of CAA in the iPD cohort was higher (53%) than in controls (28%). CAA occurred more frequently in the iPD+AD (70%) sub-set than in the iPD-AD (44%) one. The progression of CAA was differentiated, with predominance of mild stage. Diminished smooth muscle actin and collagen IV expression in the vascular media with concomitant collagen III positive immunoreactivity in the intima were observed only in very severe CAA. Ultrastructural assay revealed degenerative changes in vessel smooth muscle cells and thickening of their basement membrane with the focal accumulation of amyloid fibres and fibrillar collagen in both iPD –AD and iPD+AD cases, but the most severe CAA-type changes were visible in the iPD+AD sub-set. The same type of immunoreactivity (Aβ42 positive and Aβ40 positive) of arterial CAA and parenchymal neuritic plaques, as well as capillary CAA and diffuse plaques (Aβ42 positive and Aβ40 negative), may indicate pathogenic similarities and differences between both types of degenerative changes on the one hand and time-different changes or local different processing of amyloid precursor protein on the other.